PENERAPAN STRATEGI PROMOSI KAFE LUCKY FINGER MELALUI DESAIN PROMOSI ONEWAY DI JENDELA KACA - Kelvin; Maria Beatrix; Yohanes Calvinus (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2025)
Lucky Finger is a new cafe on Jalan Arjuna Utara No. 7, West Jakarta, that serves quality coffee and side dishes. Adjacent to Esa Unggul University and UKRIDA Hospital, this cafe carries a minimalist concept with weekly raw material updates. Despite collecting customer feedback to improve services, the cafe faces ventilation and room temperature issues. The Word-of-Mouth Marketing (WOMM) strategy implemented is less effective in this location. To increase visibility and attract more visitors, it is necessary to install attractive banners that highlight the cafe's advantages, including color choices, easy-to-read typography, and appetizing images. This PKM activity aims to implement a new promotional strategy through banners to attract the attention of students and medical personnel from the surrounding area. The output of this activity includes the development of intellectual property rights in the form of slogans and banner designs, in order to increase visibility, attract consumer attention, and strengthen brand identity. The implementation method involved analyzing consumer visits before and after the banner installation, with an initial survey and direct observation to collect data. After installation, a follow-up survey was conducted to compare changes in visits, and responses from respondents through a questionnaire. The results of this PKM activity showed that the majority of respondents paid attention to the promotion and considered the design attractive (64.3%). The promotional design on the glass window made it easier for respondents to find out promotional information and conveyed an aesthetic message (57.1% agreed). The questionnaire for cafe workers regarding opinions on the banner, the opinions given were positive because the results were good so that more visitors came. In addition, the design became more attractive than before because before the renovation it was a little empty, but it is more visible now because of the banner. Lucky Finger adalah kafe baru di Jalan Arjuna Utara No. 7, Jakarta Barat, yang menyajikan kopi berkualitas dan makanan pelengkap. Bersebelahan dengan Universitas Esa Unggul dan RS UKRIDA, kafe ini mengusung konsep minimalis dengan pembaruan bahan baku mingguan. Meski mengumpulkan masukan pelanggan untuk meningkatkan layanan, kafe menghadapi masalah ventilasi dan suhu ruangan. Strategi Word-of-Mouth Marketing (WOMM) yang diterapkan kurang efektif di lokasi tersebut. Untuk meningkatkan visibilitas dan menarik lebih banyak pengunjung, perlu dipasang spanduk menarik yang menonjolkan keunggulan kafe, termasuk pilihan warna, tipografi yang mudah dibaca, dan gambar menggugah selera. Kegiatan PKM ini bertujuan menerapkan strategi promosi baru melalui spanduk untuk menarik perhatian mahasiswa dan tenaga medis dari sekitar. Luaran kegiatan ini mencakup pengembangan hak kekayaan intelektual berupa slogan dan desain banner, guna meningkatkan visibilitas, menarik perhatian konsumen, dan memperkuat identitas merek. Metode pelaksanaan melibatkan analisis kunjungan konsumen sebelum dan setelah pemasangan banner, dengan survei awal dan pengamatan langsung untuk mengumpulkan data. Setelah pemasangan, survei lanjutan dilakukan untuk membandingkan perubahan kunjungan,dan respon dari para responden melalui kuesioner. Hasil kegiatan PKM ini menunjukkan bahwa mayoritas responden memperhatikan promosi dan menganggap desain menarik (64.3%). Desain promosi pada jendela kaca memudahkan responden untuk mengetahui informasi promosi dan memberikan pesan estetika (57.1% menyatakan setuju). Kuesioner bagi pekerja kafe terkait opini pada banner, opini yang diberikan positif karena hasil bagus sehingga lebih banyak pengunjung yang datang. Selain itu, desain menjadi lebih menarik dari sebelumnya karena sebelum direnovasi sedikit kosong, tapi lebih terlihat saat ini karena adanya banner.